The Sustainable Aspect of Safety in Architectural Early Design: An Introduction to Prevention through Design (PtD) Concept - Natasha Khalil; Samsudin, Nor Syamimi; Zainonabidin, Azman (International Journal of Sustainable Construction Engineering and Technology, 2022)
Architects must have an adequate and relevant understanding of Prevention through Design (PtD) to execute essential design decisions during the early design stage. The understanding of PtD as a proactive safety intervention throughout the design process has been supported in various studies, but there has been little research incorporating PtD in design practices by the architect and provisional architectural safety design parameter on the Occupational Safety and Health (OSH) matters, thus, leading to the gap in this study. Considering thePtD concept as part of the sustainable strategy into the architectural early design stages may significantly enhance the building’s life cycle and safety performance, particularly during the operational and maintenance phase of the building projects. Therefore, the systematic review was motivated by the belief that the early architectural design stage is one of the key factors improving safety performance in the practice of PtD. This review begins by analysing literature from 2011 to 2021 with relevant keywords related to the architectural design aspect that contributes to building safety performance, followed by characterising the safety aspect at the early architectural design stage. The findings were identified and clustered into the following five categories of the architectural design parameters: 1) Site planning, 2) Space Planning, 3) Building envelope, 4) Design for Visibility, and 5) Environmental Design Parameters. This finding is hope to be able to providean architectural frame of reference on Occupational Safety and Health (OSH) matters, allowing future researchers and practitioners to address sustainable aspect of safety in the early architectural design practices of PtD while optimising building safety performance across the building life cycle projects.